Fibroblast growth factor‐1 attenuates TGF‐β1‐induced lung fibrosis. Issue 2 (26th September 2016) - Shimbori, Chiko; Bellaye, Pierre‐Simon; Xia, Jiaji; Gauldie, Jack; Ask, Kjetil; Ramos, Carlos; Becerril, Carina; Pardo, Annie; Selman, Moises; Kolb, Martin
Abstract: Idiopathic pulmonary fibrosis (IPF) is characterized by progressive fibroblast and myofibroblast proliferation, and extensive deposition of extracellular matrix (ECM). Fibroblast growth factor‐1 (FGF‐1) belongs to the FGF family and has been shown to inhibit fibroblast collagen production and differentiation into myofibroblasts, and revert epithelial–mesenchymal transition by inhibiting TGF‐β1 signalling pathways. However, the precise role of FGF‐1 in pulmonary fibrosis has not yet been elucidated. In this study, we explore the mechanisms underlying the anti‐fibrogenic effect of FGF‐1 in pulmonary fibrosis in vitro and in vivo by prolonged transient overexpression of FGF‐1 (AdFGF‐1) and TGF‐β1 (AdTGF‐β1) using adenoviral vectors. In vivo, FGF‐1 overexpression markedly attenuated TGF‐β1‐induced pulmonary fibrosis in rat lungs when given both concomitantly, or delayed, by enhancing proliferation and hyperplasia of alveolar epithelial cells (AECs). AdFGF‐1 also attenuated the TGF‐β1 signalling pathway and induced FGFR1 expression in AECs. In vitro, AdFGF‐1 prevented the increase in α‐SMA and the decrease in E‐cadherin induced by AdTGF‐β1 in normal human lung fibroblasts, primary human pulmonary AECs, and A549 cells. Concomitantly, AdTGF‐β1‐induced Smad2 phosphorylation was significantly reduced by AdFGF‐1 in both cell types. AdFGF‐1 also attenuated the increase in TGFβR1 protein and mRNA levels in fibroblasts. In AECs, AdFGF‐1 decreased TGFβR1 protein by favouring TGFβR1 degradation through the caveolin‐1/proteasome pathway. Furthermore, FGFR1 expression was increased in AECs, whereas it was decreased in fibroblasts. In serum of IPF patients, FGF‐1 levels were increased compared to controls. Interestingly, FGF‐1 expression was restricted to areas of AEC hyperplasia, but not α‐SMA‐positive areas in IPF lung tissue. Our results demonstrate that FGF‐1 may have preventative and therapeutic effects on TGF‐β1‐driven pulmonary fibrosis via inhibiting myofibroblast differentiation, inducing AEC proliferation, regulating TGF‐β1 signalling by controlling TGFβR1 expression and degradation, and regulating FGFR1 expression. Thus, modulating FGF‐1 signalling represents a potential therapy for the treatment of pulmonary fibrosis. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.